2012
DOI: 10.1901/jaba.2012.45-763
|View full text |Cite
|
Sign up to set email alerts
|

Correspondence Between Single Versus Daily Preference Assessment Outcomes and Reinforcer Efficacy Under Progressive‐ratio Schedules

Abstract: Research has suggested that a daily multiple‐stimulus‐without‐replacement (MSWO) preference assessment may be more sensitive to changes in preference than other assessment formats, thereby resulting in greater correspondence with reinforcer efficacy over time (DeLeon et al., 2001). However, most prior studies have measured reinforcer efficacy using rate of responding under single‐operant arrangements and dense schedules or under concurrent‐operants arrangements. An alternative measure of reinforcer efficacy in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 19 publications
3
32
0
Order By: Relevance
“…These correlations were moderate across a relatively short period of time (i.e., 5 days) and small across longer spans (i.e., 90 days), suggesting that student preference was variable. This is not inconsistent with previous research demonstrating instability in individual preference both within and between assessment methods (Call, Trosclair-Lasserre, Findley, Reavis, & Shillingsburg, 2012;Mason, McGee, Farmer-Dougan, & Risley, 1989;Zhou, Iwata, Goff, & Shore, 2001). These data highlight the importance of frequent assessment of stimulus preference across individual, and group methodologies and researchers should continue to investigate solutions to address these fluctuations across settings.…”
Section: Discussionsupporting
confidence: 61%
“…These correlations were moderate across a relatively short period of time (i.e., 5 days) and small across longer spans (i.e., 90 days), suggesting that student preference was variable. This is not inconsistent with previous research demonstrating instability in individual preference both within and between assessment methods (Call, Trosclair-Lasserre, Findley, Reavis, & Shillingsburg, 2012;Mason, McGee, Farmer-Dougan, & Risley, 1989;Zhou, Iwata, Goff, & Shore, 2001). These data highlight the importance of frequent assessment of stimulus preference across individual, and group methodologies and researchers should continue to investigate solutions to address these fluctuations across settings.…”
Section: Discussionsupporting
confidence: 61%
“…Results also may be limited to the particular PR schedules used in the current study. We selected PR schedules based on prior research findings that suggested that PR schedules are more sensitive than FR schedules to differences in reinforcement effects (e.g., Call et al, ; Tiger et al, ). The PR schedule values were selected somewhat arbitrarily but with consideration of the time available for sessions and the possibility of encountering problems with too‐rapid ratio strain.…”
Section: Discussionmentioning
confidence: 99%
“…The number of responses required to obtain the reinforcer increased following each trial. For initial participants, we started with larger response‐requirement increments for the PR schedules, based on previous research in this area (e.g., Call, Trosclair‐Lasserre, Findley, Reavis, & Shillingsburg, ; Tiger et al, ). The increments were reduced for Tom and Oscar to determine if more gradual changes in the schedule requirements would increase sensitivity to the independent variable.…”
Section: Methodsmentioning
confidence: 99%
“…Although all participants showed the emergence of vocal speech, there was significant variance between independent and prompted vocalizations, with stable and consistent responding for independent speech never being achieved. Previous research has suggested that daily preference assessments may offer a better account for potential momentary changes in preference, leading to more effective reinforcers (Call, Trosclair‐Lasserre, Findley, Reavis, & Shillingsburg, ; DeLeon et al, ). Additionally, the authors did not assess for the emergence of novel untrained vocalizations, such as requests related to stimuli not included in the study.…”
mentioning
confidence: 99%